Réponses

2012-11-15T16:06:39+01:00

A=15x-12x²-3-28x²+12x

   = -40x²+27x-3

B = 10x²-4x+4x-14x²-2x

    = -4x²-2x

C = 6-2x(7-6x-2)+10-6x

   = 6-2x(5-6x)+10-6x

   =16-10x+12x²-6x

   = 12x²-16x+16

D = x-x(3-7+x)-2x-(4x-x+2)

   = -x-x(x-4)-3x-2

   = -4x - 2 -x²+4x

   = -2-x²

mais c'était très facile,de la distributivité simple. tu devrais te poser des questions...

2012-11-15T16:08:53+01:00

 

A=15x-12x²-3-28x²+12x

   = -40x²+27x-3

B = 10x²-4x+4x-14x²-2x

   = -4x²-2x

C = 6-2x(7-6x-2)+10-6x

   = 12x²-16x+16

D = x-x(3-7+x)-2x-(4x-x+2)

   = -2-x²